2020
DOI: 10.4102/sajhrm.v18i0.1211
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between executive pay and company financial performance in South African state-owned entities

Abstract: Orientation: Executive pay has been increasing; however, company performance has not been increasing proportionally. This could be due to an agency problem, resulting in executive pay not aligning with the shareholders’ desired company performance.Research purpose: The purpose of this research was to establish if there was a relationship between the total pay of the chief executive officer and their company’s financial performance in South African Schedule 2 state-owned entities (SOEs).Motivation for the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…It should be noted that inflation was not considered as research investigating the relationship between CEOs' remuneration and company performance used nominal data and not constant data (e.g. Carlson & Bussin, 2020).…”
Section: Key Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that inflation was not considered as research investigating the relationship between CEOs' remuneration and company performance used nominal data and not constant data (e.g. Carlson & Bussin, 2020).…”
Section: Key Resultsmentioning
confidence: 99%
“…The descriptive statistics further suggest that even though SOEs financial performance declined in the years after the economic crisis (except for turnover and liquidity), CEOs' remuneration increased. It is interesting to note that Carlson and Bussin (2020) in their study in the SOE environment, observed an average growth in total CEOs' pay of 28.68% over the period 2009 to 2016. This could suggest that South African SOEs did not have a good corporate governance practice in place regarding the level or structure of CEOs' remuneration.…”
Section: Descriptive Statisticsmentioning
confidence: 97%
See 3 more Smart Citations